Kinerja Keuangan Perusahaan Sebelum dan Sesudah Pengumuman Right Issue di Bursa Efek Indonesia - Khuzaimah, Khuzaimah; Musrizal, Musrizal; Jamaluddin, Jamaluddin (Aceh Cooperative Care, 2024)
This research aims to determine the differences in company financial performance as proxied by the level of profitability, liquidity and level of leverage between before and after the rights issue on the IDX. The research was carried out quantitatively using data sourced from www.idx.co.id (2023). The research results state that ROA between before and after carrying out the rights issue has a significant difference. However, there is no difference in the Current Ratio (CR) variable before and after carrying out the rights issue. Likewise, there is no difference in the Debt Equity Ratio before and after carrying out the rights issue.